Microbial and biogeochemical responses to changing precipitation patterns in grassland ecosystems - Evans, Sarah E., author; Wallenstein, Matt, advisor; Burke, Indy, advisor; Lauenroth, Bill, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2012)
Global circulation models predict that precipitation patterns in grasslands will both intensify and be characterized by more severe drought in the future. In these systems, the availability of water strongly controls ecosystem function, so changes in precipitation are likely to significantly alter biological communities and biogeochemical dynamics. Since these biogeochemical changes could feed back on climate drivers by influencing regional to global scale energy and water balance, predicted changes in grassland precipitation call for a better understanding of relationships between water availability and grassland biogeochemical dynamics. My dissertation aimed to address how changing rainfall patterns affect biogeochemical cycling and soil microbial communities in grasslands. I first tested the generality of controls over soil organic matter storage in temperate grasslands by studying existing spatial gradients in soil carbon and nitrogen, as they relate to the spatial variation in average precipitation and temperature, and soil texture. I found that statistical models developed in US grasslands overestimated soil organic carbon and underestimated soil organic nitrogen in Chinese grasslands. However, when I incorporated nitrogen deposition and historical land use using a simulation model, it resulted in more accurate model estimates for this region. This work suggests that nitrogen deposition and historical land use legacies may need to be considered to accurately describe biogeochemical dynamics in Chinese grasslands and better predict the vulnerability of global carbon stocks to loss. Responses of ecosystems to changes through time are often somewhat different than relationships gleaned from large-scale spatial gradients. At the local scale, I found that an 11-year drought can significantly alter biogeochemical and ecosystem dynamics in the highly drought-resistant shortgrass steppe. Here, soil inorganic nitrogen availability increased up to 4-fold in plots receiving 25% of summer precipitation. This accumulation of nitrogen under drought may explain the higher plant tissue nitrogen and N2 flux observed under recovery. A more "open" nitrogen cycle that I observed following severe drought could affect the impact of drought on grassland ecosystems, as well as the timescale of recovery. Soil microbial community composition was also altered by this 11-year drought manipulation in the shortgrass steppe, and these differences persisted even after communities were subject to the same moisture conditions for 36 hours in the lab. In this lab experiment, I also identified specific microbial groups that grew under a certain moisture levels, presenting evidence of moisture niche partitioning in microbial communities. However, this niche differentiation wasn't realized in the field; communities that grew under dry conditions in the lab were not similar to those that emerged under long-term drought plots. Overall, this work suggests that contrary to previous assumptions, microbial communities display legacies from long-term field treatments, and that although soil moisture has the potential to drive microbial community composition through niche partitioning, this factor may not always be the primary driver of long-term community composition. Microbial communities were also sensitive to altered precipitation timing in the tallgrass prairie. In addition, communities that were subject to intensified precipitation patterns in the field respired less than control soils after laboratory rewetting events, but respiration rates of the different field treatments converged after 100 days under the same conditions. Surprisingly, species composition of these communities was more sensitive to drying and rewetting pulses in the lab than those from the control. Together, these results show that microbial communities display legacies to altered precipitation timing, in addition to drought, but community composition is not necessarily tightly linked to respiration. Overall, my dissertation work suggests that grasslands will be sensitive to extreme shifts in precipitation, and that biogeochemical and microbial responses could influence how grasslands are altered under future precipitation regimes. However, my work also shows that precipitation is not the only factor controlling biogeochemical and microbial community dynamics in grasslands, even under rainfall manipulations and across precipitation gradients. Therefore, the response of grasslands to other environmental factors - that shift with precipitation changes or are predicted to change independently - should not be overlooked.
Keywords: carbon; climate change; drought; microbial community; nitrogen; semiarid ecosystem